Incorporation of building information modelling (BIM) in Malaysian higher education institutions: a review / Juliana Brahim, Seri Nanisa Sima Yusoff and Zainidi Mat Yusoff. - Brahim, Juliana; Yusoff, Seri Nanisa Sima; Mat Yusoff, Zainidi (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2021)
Building Information Modelling (BIM) is initiated for the sake of managing construction projects effectively and efficiently. However, the adoption of BIM in Malaysian construction industry is still low because of lack of awareness among professionals and Architecture, Engineering, and Construction (AEC) undergraduates. This paper aims to evaluate the current adoption of BIM in syllabus among higher education institutions (HEIs). The methodology of this paper is based on literature review regarding BIM syllabus adopted in HEIs. The findings reveal that BIM in Malaysia is still lagging in practice and literature taught for academic aspects respectively compared to other developed countries such as United Kingdom and Lithuania. From the current adoption of BIM in Malaysian HEIs syllabus, it can be concluded that fully stand-alone BIM module in Malaysian HEIs is crucial which consequently hampering the production of high-quality BIM expertise that master in methodology and 3D modelling skills.